PROPOSAL OF ALGORITHM FOR ROUTE OPTIMIZATION - Sousa, Robert Ramon de Carvalho; Costa, Abimael de Jesus Barros; Carvalho, Eliezé Bulhões de; Paranaíba, Adriano; Sandoval, Daylyne Maerla (Colloquium Exactarum. ISSN: 2178-8332, 2017)
This article uses “Six Sigma” methodology for the elaboration of an algorithm for routing which is able to obtain results more efficient than those from Clarke and Wright´s algorithm (1964) in situations of random increase of demands of product delivery before the incapability of the increase of service level. In some situations the algorithm proposed obtained results more efficient that Clarke and Wright´s model (1964). The key factor was the reduction of the number of mistakes (one way routes) and the level of result variation.